1996
DOI: 10.1002/bjs.1800830413
|View full text |Cite
|
Sign up to set email alerts
|

Radical surgery for advanced gallbladder carcinoma

Abstract: Forty-four patients with advanced gallbladder carcinoma (18 with stage pT3 and 26 with stage pT4 of the Union Internacional Contra la Cancrum classification) were aggressively managed by extended heptatic resection in 33 patients, bile duct resection in 28, pancreaticoduodenectomy in seven, gastrointestinal resection in eleven and portal vein resection and reconstruction in seven. Adjacent organ involvement was classified as follows: type I, hepatic involvement with or without gastrointestinal invasion (Ia, Ib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 12 publications
5
110
2
5
Order By: Relevance
“…Moreover, in the same series (8)(9)(10)(11)(12), some jaundiced patients appeared to benefit from surgery in terms of survival following resection: with a mean 3-year survival of 20% and some real survivors at 3 and 5 years (8, 11), results never obtained in the subgroup of non-resected jaundiced patients. In the present series, overall survival was better in resected jaundiced patients than in non-resected jaundiced patients (p=.001) and the 3-year overall survival rates of 19% was comparable to the overall survival of resected patients with pancreatic adenocarcinoma in whom the principle of curative R0 resection has been established.…”
Section: Some Jaundiced Patients Appeared To Benefit From Surgerymentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, in the same series (8)(9)(10)(11)(12), some jaundiced patients appeared to benefit from surgery in terms of survival following resection: with a mean 3-year survival of 20% and some real survivors at 3 and 5 years (8, 11), results never obtained in the subgroup of non-resected jaundiced patients. In the present series, overall survival was better in resected jaundiced patients than in non-resected jaundiced patients (p=.001) and the 3-year overall survival rates of 19% was comparable to the overall survival of resected patients with pancreatic adenocarcinoma in whom the principle of curative R0 resection has been established.…”
Section: Some Jaundiced Patients Appeared To Benefit From Surgerymentioning
confidence: 90%
“…In the light of these results, the authors concluded that "These data do not support routine operative exploration of patients with jaundice secondary to gallbladder cancer". However, several series experienced teams did not report such a poor outcome and showed that some jaundiced patients obtained improved survival following resection of GBC (8)(9)(10)(11)(12). A subgroup of jaundiced patients may therefore benefit from resection.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node metastasis within the hepatoduodenal ligament, therefore, may facilitate extensive cancer spread through the liver. Miyazaki et al 12 showed prospects for survival in extensively resected cases with bile duct involvement significantly worse than in cases with direct invasion of the liver. This less favorable outlook for survival owing to earlier recurrence may be attributed to the portal tract spread through the involvement of hepatoduodenal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…T4 tumors are those that invade the main portal vein or hepatic artery, and those that invade two or more extrahepatic organs or structures. T4 tumors are usually not amenable to surgical resection, or carry substantial morbidity and mortality when approached surgically [22].…”
Section: T3 and T4 Gbcmentioning
confidence: 99%